HUBUNGAN AKTIVITAS FISIK TERHADAP PREDIKSI VO2MAKS PADA CALON JEMAAH HAJI LANSIA DI KBIH KODAM I BUKIT BARISAN KOTA MEDAN - ALIYYUL HALIM SARAGIH; ELMAN BOY S (JURNAL ILMIAH KOHESI, 2021)
In accordance with aging, there will be physical, psychological, and social deterioration of the elderly which can be describedthrough four stages, namely weakness, functional limitations, disability, and inhibition that will occur simultaneously with theaging process. Hajj is a physical worship, besides when performing the pilgrimage prospective pilgrims will also be facedwith extreme dimensions and temperatures, so that it requires fitness. Many factors can affect the level of fitness one ofwhich is physical activity. To determine the relationship between physical activity and VO2Maks prediction on elderly Hajjpilgrims at KBIH Kodan I Bukit Barisan, Medan City. The design of this study was non-experimental using a correlativeanalytic method with a cross sectional approach. Sampling was done by purposive sampling. Data collection was takenthrough an IPAQ questionnaire interview and a 6 minute road test. Based on the results of the analysis test using the ChiSquare test, the p value was 0.019 (p <0.05), which means that there was a significant relationship between physical activityand prediction of VO2Max on Prospective Elder Pilgrims at KBIH Kodam 1 Bukit Barisan, Medan. There is a significantcorrelation between physical activity and VO2Maks prediction in elderly prospective pilgrims at KBIH Kodam 1 Bukit Barisan,Medan.